Aquatic Fitness Professional Manual - Aquatic Exercise Association (Champaign, Illinois Human Kinetics, 2018)
Aquatic fitness is as popular as ever. A proven fitness activity, it is challenging, fun, and immensely rewarding for all age groups and abilities. With reduced-impact options for group exercise, small-group fitness programs, and personal training, there is little wonder why expert aquatic fitness instructors are in demand. As the primary preparation resource for the certification exam of the Aquatic Exercise Association (AEA), Aquatic fitness professional manual, seventh edition, provides you the tools to develop your expertise. With contributions from 19 industry experts with decades of experience, you will learn how to energize your teaching with techniques and programs based on many popular fitness formats, such as kickboxing, yoga, boot camp, pilates, walking and jogging, circuits, intervals, and sport-specific training. You'll also find updated research on shallow- and deep-water exercise, specialty equipment, the latest interval training techniques, working with special populations, and water safety guidelines. Nowhere else will you find the fitness applications and comprehensive programming you need in one convenient resource. Aquatic Fitness Professional Manual contains essential foundational information on the components of physical fitness, group fitness teaching techniques, and AEA Standards and Guidelines. Prepare for the AEA Aquatic Fitness Professional Certification exam and expand your teaching and career opportunities by cultivating the critical skills for leading safe, enjoyable, and effective aquatic exercise programs.
Chapter 1 Physical fitness -- Chapter 2 Exercise anatomy -- Chapter 3 Exercise physiology -- Chapter 4 Movement analysis -- Chapter 5 Exercise motivation and behavior -- Chapter 6 Physical laws as applied to the aquatic environment -- Chapter 7 Pool environment and design -- Chapter 8 Shallow-water exercise -- Chapter 9 Deep-water exercise -- Chapter 10 Aquatic exercise leadership -- Chapter 11 Aquatic exercise programming -- Chapter 12 Special populations and health conditions -- Chapter 13 Safety, emergencies, injuries, and instructor health -- Chapter 14 Basic nutrition and weight management -- Chapter 15 Business issues and legal considerations
Includes bibliographical references and index
Keywords: Aquatic exercises